BIOAKTIF ALAMI DARI TAPAK DARA (Catharanthus roseus) TERHADAP PENYAKIT HIPERTENSI DENGAN PENDEKATAN DASAR PENELITIAN IN SILICO - Taihuttu, Monalisa Pertiwi Jeriska; Watung, Fernando A; Lathif, Yudrik (Pattimura University, 2024)
Ajmalicine is a natural secondary metabolite compound found in the Catharanthus roseus plant, which has potential as an antihypertensive agent. Docking simulations were used to explore the molecular interactions between Ajmalicine and its identified target protein, the Alpha-2A adrenergic receptor, using three servers: PharmMapper, SwissTargetPrediction, and SuperPred. The analysis was supported by software such as PyMOL and LigPlus, Discovery Studio 2016 Client, and PyRx 0.8. The results showed that Ajmalicine interacts with the target protein, and this interaction was compared with a control compound, Clonidine, a chemical already used as an antihypertensive drug. The findings revealed that Ajmalicine binds to the same site on the target protein as Clonidine.